(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Students therefore utilise social media to strengthen their abilities in particular for students. What is the impact of social media on creative writing of students in this study? And why students utilise academic abbreviations and acronyms. The results suggest that most students have found that social media have a little influence on their formal writing, and the major reasons behind the use of academic abbreviations are to gain time, make the communication process easier, become a habit and forget about word form. In order to explore the influence of the students’ creative writing skills, The results revealed that the writing of high school students with the good impacts overweighs the negative effects of digital social media has various influences. The results indicated that both students and teachers may engage in groups where they can exchange ideas, share resources linked to their courses and invite their students to take up jobs that can assist students improve their creative talents in writing. The 21st century has called for the development of new skills and practices in education systems that are explicit and intentional. The goal is to prepare students for the complexity of complex problems that they will face in today’s world. In 2009, the OECD urged governments to improve the skills and competencies of their students in order to prepare them for the end of compulsory schooling. Various groups like the European Commission, The Organization for Economic Cooperation, and the US National Research Council have provided rigorous research on 21st-century skills.